Discourse in Gender Studies: How Language Shapes Gender Narratives? - Azmy, Khairul; Rahman, Fadhlur; Muntasir, Muntasir (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2024)
This study explores the significance of discourse in the field of gender studies, with a specific emphasis on the ways in which language shapes and impacts perceptions of gender. The study highlights the influence of power dynamics within language, illustrating how communication strengthens conventional gender norms and prejudices. However, the substantial amount of research in this field posed difficulties in attaining a thorough understanding. Although numerous studies specifically position their work within the framework of discourse analysis, the various methodologies employed hinder a cohesive function of discourse analysis as a means of examining language and gender. This paper offers a detailed analysis of relevant theoretical frameworks, findings and discussions to gain a comprehensive understanding of how language and gender narratives interact. The study then expanded on current knowledge of gender, identity, and discourse by actively analysing and engaging with long-standing and continuing debates. The findings emphasize the possibility of using discourse to confront and change deeply embedded gender biases, promoting an equal depiction of genders through the use of language. Abstrak Artikel ini mengkaji pentingnya memahami wacana dalam studi gender. Penelitian ini memberi perhatian khusus pada cara bahasa dapat membentuk dan mempengaruhi persepsi gender. Studi ini menunjukkan pengaruh dinamika kekuasaan dalam bahasa, yang menunjukkan bagaimana wacana dapat menunjukkan dan memperkuat norma dan prasangka gender yang ada. Banyak penelitian menggunakan analisis wacana sebagai dasar kajian dinamika bahasa dan gender. Namun, berbagai pendekatan yang digunakan membuatnya tidak efektif. Penelitian ini menganalisis relevan kerangka teori untuk mendapatkan pemahaman yang lebih baik tentang bagaimana bahasa dan persepsi gender berinteraksi satu sama lain. Dengan secara aktif menganalisis dan berpartisipasi dalam perdebatan yang telah berlangsung lama dan berkelanjutan, penelitian ini meneliti dan meningkatkan pengetahuan saat ini tentang gender, identitas, dan wacana. Temuan artikel ini menekankan bahwa pendekatan wacana dapat digunakan untuk menghadapi dan mengubah bias gender yang kuat, sehingga dapat mendorong penggambaran gender yang lebih setara dan adil melalui penggunaan bahasa.